1993
DOI: 10.1002/ajmg.1320470535
|View full text |Cite
|
Sign up to set email alerts
|

Patient with double heterozygosity for achondroplasia and pseudoachondroplasia, with comments on these conditions and the relationship between pseudoachondroplasia and multiple epiphyseal dysplasia, Fairbank type

Abstract: We present a 7 1/2-year-old girl with achondroplasia and pseudoachondroplasia. Her mother has achondroplasia and her father has pseudoachondroplasia. Radiographic manifestations of these two conditions from infancy to age 6 years are outlined. The findings in this patient are compared with those of achondroplastic patients and pseudoachondroplastic patients of similar ages. Our review of radiographs of many pseudoachondroplastic patients and subsequently of those of patients with multiple epiphyseal dysplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
1
11
2
Order By: Relevance
“…This is the fourth example of double heterozygosity for achondroplasia and pseudoachondroplasia. The single case described by Langer et al [1993] and the two siblings reported by Woods et al [1994] had virtually identical radiographic findings as described here. All of the probands were initially thought to have achondroplasia (alone).…”
Section: Achondroplasia/pseudoachondroplasiasupporting
confidence: 74%
“…This is the fourth example of double heterozygosity for achondroplasia and pseudoachondroplasia. The single case described by Langer et al [1993] and the two siblings reported by Woods et al [1994] had virtually identical radiographic findings as described here. All of the probands were initially thought to have achondroplasia (alone).…”
Section: Achondroplasia/pseudoachondroplasiasupporting
confidence: 74%
“…Most double dominant skeletal dysplasias exhibit a more severe clinical phenotype than might be predicted based on the features of the individual disorders alone [Young et al, 1992;Langer et al, 1993;Kitoh et al, 1994;Woods et al, 1994;Gunthard et al, 1995], and the severe skeletal dysplasia phenotype of the PSACH/ SEDC double heterozygote is no exception. However, the PSACH/SEDC phenotype is distinct from the other described double dominant disorders in that it results from alterations in two structural components of the cartilage extracellular matrix, COMP and type II collagen.…”
Section: Discussionmentioning
confidence: 99%
“…While individually rare, the phenomenon of assortative mating based on stature has resulted in a number of case reports of patients with two dominant skeletal dysplasias [Young et al, 1992;Langer et al, 1993;Kitoh et al, 1994;Woods et al, 1994;Gunthard et al, 1995]. We have identi®ed a child who had clinical and radiographic features of combined pseudoachondroplasia (PSACH) and spondyloepiphyseal dysplasia congenita (SEDC), having inherited PSACH from his mother and SEDC from his father.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to crystallize the T3 repeats in the presence or absence of calcium have failed, perhaps indicating a highly flexible conformation. 2 Calcium binding is strongly cooperative, and the affinity is high enough that the T3 repeats should be in the calcium-saturated form in the presence of physiological extracellular calcium concentrations. Interestingly, the mutations D469⌬ and D361Y did not induce a breakdown of the cooperative system, and only 4 or 6 of the 14 calcium binding sites were lost.…”
Section: Calcium Binding Is Affected Inmentioning
confidence: 99%
“…The major clinical complication is caused by premature osteoarthritis of the weight-bearing joints (1). Both syndromes exhibit considerable clinical heterogeneity and show a broad phenotypical overlap with PSACH at the severe end of the disease spectrum and MED at the mild end of the disease spectrum (2,3). Genetic linkage to chromosome 19 was recently demonstrated for both mild and severe forms and was soon followed by the identification of mutations in cartilage oligomeric matrix protein (COMP) that cause both PSACH and MED (4,5).…”
mentioning
confidence: 99%